Same sex, different cultures: exploring gay and lesbian lives - Herdt, Gilbert H. (Westview Press, 1997)
Because homoerotic relations can be found in so many cultures, Gilbert Herdt argues that we should think of these relations as part of the human condition. This new cross-cultural study of gays, lesbians, and bisexuals around the world, Same Sex, Different Cultures provides a unique perspective on maturing and living within societies, both historical and contemporary, that not only acknowledge but also incorporate same-gender desires and relations. Examining what it means to organize "sex" in a society that lacks a category for "sex", or to love someone of the same gender when society does not have a "homosexual" or "gay/lesbian" role, Herdt provides provocative new insights in our understanding of gay and lesbians lives. Accurate in both its scientific conceptions and wealth of cultural and historical material, examples range from the ancient Greeks and feudal China and Japan to the developing countries of Africa, India, Mexico, Brazil, and Thailand, from a New Guinea society to contemporary U.S. culture, including Native Americans. For all of these peoples, homoerotic relations emerge as part of culture and not separate from history or society. In many of these groups, loving or engaging in sexual relations is found to be the very basis of the local cultural theory of "human nature" and the mythological basis for the cosmos and the creation of society. The mistake of modern Western culture, Gilbert contends, is to continue the legalization of prejudice against lesbians and gays. In this light, the book addresses the issue of "universal" versus particular practices and reveals positive role models that embrace all aspects of human sexuality. Finally, it offers knowledge of the existence of persons who have loved and have been intimate sexually and romantically with the same gender in other lands through divergent cultural practices and social roles. The most important lesson to learn from this cross-cultural and historical study of homosexuality is that there is room for many at the table of humankind.
Keywords: LGBTQIA2+; approche interculturelle; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; sciences humaines; soc2014; sociologie; système colonial; systèmes d'oppressions; thématiques

Something to tell you: the road families travel when a child is gay - Herdt, Gilbert H.; Koff, Bruce (Between men--between women, 2000)
Even now, at the end of the twentieth century, many still have difficulty standing up and saying, "I am the parent of a gay child." Something to Tell You recounts the stories of families whose lives have been touched by the discovery that a child is lesbian or gay—how it affects and influences people's perceptions of their children and even changes the self-image of parents themselves. Focusing on fifty average families—not people seen in clinics or therapy—the authors found a consistent pattern of change: first negative, then positive. Sometimes the news led parents and siblings to form stronger bonds with the child, with each other, and with other relatives and friends. In many cases, their child's partner and partner's family grew to assume an important role in their own lives. In some cases, parents and siblings discovered new meaning in their lives through speaking out or joining PFLAG (Parents, Families, and Friends of Lesbians and Gays) and becoming part of the struggle for lesbian and gay rights. The authors found that families committed to staying together are typically able to overcome the powerful obstacles imposed by society. Something to Tell You also shows the lasting and sometimes tragic consequences for families who falter in the process of integration. Unwilling to accept their child's sexuality, some parents sought to blame each other, and all too often their own relationships unraveled as a result. Others who failed to tell close friends sometimes lost those friends through keeping secrets. Parents who neglected to form bonds with their child's partner fostered climates of alienation that persisted for years. A richly diverse collection of family stories, Something to Tell You is a book that will help break down widespread prejudice and put an end to destructive cultural myths. It affirms families' highest aspirations toward active love for their gay children, showing the steps to take toward new levels of support, solidarity, and love.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; famille; hétérosexisme; patriarcat; premier cycle; relations familiales; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis